Polyphenol intake and differentiated thyroid cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort - Zamora-Ros, R; Cayssials, V; Franceschi, S; Kyrø, C; Weiderpass, E; Hennings, J; Sandström, M; Tjønneland, A; Olsen, A; Overvad, K; Boutron-Ruault, M-C; Truong, T; et al. (Wiley, 2019)
Polyphenols are bioactive compounds with several anticarcinogenic activities; however, human data regarding associations with thyroid cancer (TC) is still negligible. Our aim was to evaluate the association between intakes of total, classes and subclasses of polyphenols and risk of differentiated TC and its main subtypes, papillary and follicular, in a European population. The European Prospective Investigation into Cancer and Nutrition cohort included 476,108 men and women from 10 European countries. During a mean follow‐up of 14 years, there were 748 incident differentiated TC cases, including 601 papillary and 109 follicular tumors. Polyphenol intake was estimated at baseline using validated center/country‐specific dietary questionnaires and the Phenol‐Explorer database. In multivariable‐adjusted Cox regression models, no association between total polyphenol and the risks of overall differentiated TC (HRQ4 vs. Q1 = 0.99, 95% confidence interval [CI] 0.77–1.29), papillary (HRQ4 vs. Q1 = 1.06, 95% CI 0.80–1.41) or follicular TC (HRQ4 vs. Q1 = 1.10, 95% CI 0.55–2.22) were found. No associations were observed either for flavonoids, phenolic acids or the rest of classes and subclasses of polyphenols. After stratification by body mass index (BMI), an inverse association between the intake of polyphenols (p‐trend = 0.019) and phenolic acids (p‐trend = 0.007) and differentiated TC risk in subjects with BMI ≥ 25 was observed. In conclusion, our study showed no associations between dietary polyphenol intake and differentiated TC risk; although further studies are warranted to investigate the potential protective associations in overweight and obese individuals.